WORK MOTIVATION AS A CHANGING FACTOR IN THE EFFECTS OF ORGANIZATIONAL CULTURE AND COMPENSATION ON EMPLOYEE PERFORMANCE: (Case Study of Family Businesses in Indonesia) - Erfan Effendi; Dewi Tri Wijayati Wardoyo; Jun Surjanti (Transpublika Publisher, 2024)
Human resources are essential assets for any organization, highlighting the crucial role of employee performance in achieving success. This study aims to investigate the impact of organizational culture and compensation on employee performance through work motivation at PT. XYZ, a multinational family business specializing in maintenance services and spare parts sales for conveyors, with operations in East and Central Java. Utilizing a quantitative approach, the research employs the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique via Smart-PLS 3.0 software. The study involved 95 respondents selected from a total of 125 employees through purposive sampling, with data collected via questionnaires distributed across five office locations in Gresik, Tuban, Paiton, Jepara, and Batang. Findings reveal that work motivation significantly mediates the relationship between organizational culture, compensation, and employee performance. The study contributes theoretically by demonstrating that work motivation is a crucial factor in enhancing employee performance through organizational culture and compensation, highlighting its role as a key variable in improving performance outcomes.